Arrastão ou lagarteado? Dinâmicas em torno da prática docente na Fundação CASA - Olic, Mauricio Bacic [UNESP] (FapUNIFESP (SciELO), 2017)
This article aims to reflect on the relation between ethnographic doing and teaching within institutions of social control. For this, it explores the researcher's position as a teacher who works in detention units of Fundação CASA, where socio-educational measures provided by Estatuto da Criança e do Adolescente (ECA - Child and Adolescent Statute) are applied to adolescents who commit offenses. Involvement in the routine of the institution allows the narrative to be constructed in a symmetrical movement, in which the teacher can experience and be affected by the different devices that seek to territorialize the units. Because that is a social control environment marked by conflicting relations, symmetrical ethnographic description assumes a tense perspective, since in the teaching practice and the construction of bonds within the institution there is a number of risks and dangers, which can lead teachers to be coopted by normative forces of the collective of officials and adolescents. When this happens, the teacher fails to build a mediating attitude of symmetrization, and becomes an intermediary who strengthens the collectives that seek to dominate the institutional routine. Thus, teaching at Fundação CASA units is a risky exercise, in that at any time the teacher can become an arrastão or a lagarteado. In the first case, he becomes just another operator of institutional norms, and, on the second, the teacher loses the limit of involvement with adolescents and starts to act according to their will.
Arrastão or lagarteado? Dynamics of teaching at Fundação CASA
Keywords: Ethnography; Fundação CASA; Socio-educational measures; Symmetry; Teaching practice